The Iloilo river development history in a changing landscape, 1855-1937 - Funtecha, Henry F. (2003)
Rivers are the streams of life. They maintain life sustaining matters, they serve as arteries of commerce and trade, as well as instruments in the development of agriculture. Furthermore, they encouraged migrations, leading to the rise of communities and the spread of cultures and technology. This paper looks at the role of Iloilo River in the development of the town of Iloilo into a city and the transformation of its physical environment from the opening of its port to foreign trade in 1855 up to its designation as a chartered city in 1937. Library research, interviews, and actual field visits/surveys were used to gather relevant information.